2006
DOI: 10.1007/s10800-006-9168-1
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen evolution on Ni/WC composite coatings

Abstract: The catalytic activity for the hydrogen evolution reaction (HER) of Ni/WC composites obtained by electrochemical deposition of nickel from a conventional Watt's bath, using two different ways of depositing the WC particles, was investigated. All the composite coatings exhibited electrocatalytic activity for the HER larger than that of pure Ni in both alkaline and acid solution. The activity increased with increasing content of WC in the coating and, in the pulsed current regime, with increasing frequency of pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…The present work focused on the role of Ni in the catalytic activity of Pt towards the HER and HOR. This cheap and abundant transition metal is thermodynamically stable in alkaline medium and can catalyze water reduction with high overpotentials . Carbon‐supported Pt x Ni 1− x electrode materials were prepared by the bromide anion exchange (BAE) method, which is a surfactant‐free, simple, chemical‐synthesis approach that avoids inhibition of catalytic sites by long‐chain organic compounds .…”
Section: Introductionsupporting
confidence: 84%
“…The present work focused on the role of Ni in the catalytic activity of Pt towards the HER and HOR. This cheap and abundant transition metal is thermodynamically stable in alkaline medium and can catalyze water reduction with high overpotentials . Carbon‐supported Pt x Ni 1− x electrode materials were prepared by the bromide anion exchange (BAE) method, which is a surfactant‐free, simple, chemical‐synthesis approach that avoids inhibition of catalytic sites by long‐chain organic compounds .…”
Section: Introductionsupporting
confidence: 84%
“…On correlating the hardness value of composites from amount of WC incorporated in the deposits at various current densities, it is observed that hardness value increases with the WC in the deposits. A proportionately large increment beyond 3 Adm -2 could be the result of increased hydrogen adsorption due to presence of WC [39] in deposits and measured hydrogen in composite (17.74 ppm) strongly supports the trend. Microhardness values were also measured at 10 and 20 gL -1 of WC in the bath at constant current density of 3 A dm -2 .…”
Section: Surface Morphological Studiessupporting
confidence: 64%
“…Hence, it is of both scientific and commercial interests to develop alternative catalysts that are more abundant and economical. The alternative materials typically include Raney Ni and Ni alloys, which are generally used as the HER catalysts in alkaline electrolytes. MoS 2 nanoparticles , and their analogues have been suggested as promising HER catalysts, but they often operate in an acidic environment.…”
Section: Introductionmentioning
confidence: 99%